Avtomatska kontrola logične konsistence 3D baze mestnega jedra - Radovan, Dalibor (Geodetski vestnik, 2001)
Urban planning and real estatye GIS applications include visualization and analysis of objects, especially buildings, geocoded in three dimensions. Data must be free of topologic errors. Municipal community of Ljubljana is building 3D city model for which topologic and geometric rules for data acquisition and logical consistency assurance were formed. Computer software for automatic topology and geometry checking in 3D was elaborated and tested. Visualization of 3D city model is presented in MS Internet Explorer
Keywords: deformacijska analiza; geodesy; geodezija; kontrola kvalitete; topologija